RASPBERRY PI 3 BASED AUTOMATIC DOOR LOCK SECURITY SYSTEM WITH CAMERA AND SMARTPHONE INTEGRATION - Dwirama, Ribelta; Ariyos, Deded Elviyan; Fakhri, Albeni (Rang Teknik Journal, 2025)
Theft cases are the most prevalent crime in Indonesia, with various variations in each case. One type of theft that often occurs in residential areas is breaking into houses, which can happen due to weak traditional security systems. To address this issue, an adaptive and technology-based home security system is required. Advancements in technology have driven innovation in enhancing home security systems, one of which is the “Automatic Door Lock Security System Based on Raspberry PI3 with Camera and Smartphone Integration.” This research aims to develop a security system that allows users to monitor the status of their front door in real-time and control it at any time using a smartphone in a practical and efficient manner. This device uses an application tailored to user needs on a smartphone, with input from a SW420 vibration sensor for security detection, a push button for the doorbell, and a webcam to display the door's status in real time. The Raspberry Pi 3 serves as the microcontroller, with output via a buzzer as an alarm and an MG996R servo motor for opening and locking the door. The research process began with modifying the door handle according to requirements and testing the app's connection with the microcontroller, testing the SW420 vibration sensor's readings, testing the webcam, and testing the MG996R servo motor to operate the door lock and handle. Based on the research results, the app can control the device in real-time at a distance of 1m to 15m. The system is designed such that when the SW420 sensor detects vibrations deemed hazardous, the Raspberry Pi 3 sends a danger notification to the user via smartphone and also triggers a buzzer on the active door as a danger signal. The user can then monitor the area around the door and open or lock the door via smartphone.Keywords: Raspberry Pi 3, SW420 Vibration Sensor, Security System, MG996R Servo, Smartphone